(untitled) (Academic Journal of Internal Affairs, 2019)
Ninety years ago, Howard B. Gill laid the physical and criminal psychological groundwork of a new prison in the city Norfolk of the State Massachusetts, which has been under operation until today. The criminal pedagogical views of the founder on punishment and function of the captives’ council and the captives’ constitution are durable and futuristic. This model will be presented by the author.